Verktyg för panninspektion - Marknadsundersökning och utvärdering - Eliasson, Markus; Saury, Olivia (My University, 2017)
Inspection and control of major industrial boiler plants is a complex, time-consuming and costly process. Optimizing the process, minimizing the duration of shutdowns or interruptions in production is necessary. In this study we review tools and methods for boiler inspection with the purpose of improving the inspection process. We have listed a number of methods and tools that can potentially be used for boiler inspection and evaluated them based on usability, user-friendliness and safety. We have observed and documented how the work is carried out during the production shutdown of a recovery boiler. Finally, we have compared information retrieved from a visual inspection with that from an examination with a drone in a CFB-boiler. The following boiler tools and methods are listed and described in the result section: drones, virtual reality, communication tools, climbing robots, climbing technology, 360-camera and 3D laser technology. For each tool or method, we describe regulation and training requirements if relevant, as well as manufacturers, suppliers and relevant specifications. We conclude that drones are suitable as tools to complement other methods for streamlining inspection, but that training and special skills are required to handle them. Industrial rope access (climbing technology) can also be useful in certain contexts, but require trained personnel. Other tools described in the study are interesting but need to be adapted and evaluated before they can be put into systematic use.
Keywords: Farkostteknik; Transport; Vehicle Engineering; Transport